2021
DOI: 10.1007/s11196-021-09840-y
|View full text |Cite
|
Sign up to set email alerts
|

The Global Regulation of “Fake News” in the Time of Oxymora: Facts and Fictions about the Covid-19 Pandemic as Coincidences or Predictive Programming?

Abstract: The beginning of the twenty-first century saw an apparent change in language in public discourses characterised by the rise of so-called "essentially oxymoronic concepts", i.e., mainly oxymora and paradoxes. In earlier times, these rhetorical figures of speech were largely reserved for the domain of literature, the arts or mysticism. Today, however, many new technologies and other innovations are contributing to their rise also in the domains of science and of law. Particularly in law, their inherent contradic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…The Global Web Index 2020 report found that ‘using social media to stay up‐to‐date with news and current events is the top reason for logging in globally’ (Trifonova, 2021). Social media plays a gatekeeper role and constantly shares and disseminates news and information that are crucial for a functioning political system and democracy (Beckerle et al, 2021; Neuwirth, 2021). Thus, in this study, the relevance of controlling news and information flows is prioritised in deciding which social media platforms are the subjects to study.…”
Section: Methodsmentioning
confidence: 99%
“…The Global Web Index 2020 report found that ‘using social media to stay up‐to‐date with news and current events is the top reason for logging in globally’ (Trifonova, 2021). Social media plays a gatekeeper role and constantly shares and disseminates news and information that are crucial for a functioning political system and democracy (Beckerle et al, 2021; Neuwirth, 2021). Thus, in this study, the relevance of controlling news and information flows is prioritised in deciding which social media platforms are the subjects to study.…”
Section: Methodsmentioning
confidence: 99%
“…Looking for alternatives that minimize the effects of information disorder in the deliberative process, researchers point to complementary paths. Solutions involve adjustments to digital platform algorithms (van Dijk, 2017); punishment of producers of false content and limiting the advertising of such content (Manganello et al, 2020); identifying sources of disinformation (Messaoud, 2021); regulating digital media (Messaoud, 2021;Neuwirth, 2022;Polyák & Nagy, 2021;Wardle & Derakhshan, 2017), and literacy programs (Abed & Barzilai, 2023;Cook et al, 2023;Morote & Hernández, 2022;Morote Seguido, 2023;Sill et al, 2023).…”
Section: Information Disorder and Deliberative Process On Climate Changementioning
confidence: 99%
“…Na busca por alternativas que minimizem os efeitos negativos da desordem informativa, há alguns caminhos complementares. As soluções passam por ajustes nos algoritmos das plataformas digitais (van Dijk, 2017); punição dos produtores de conteúdos falsos e limitação da publicidade destes conteúdos (Manganello, Bleakley & Schumacher, 2020); o silêncio estratégico em alguns casos, evitando o 'tiro pela culatra' (Fachin et al, 2020;Uwalaka et al, 2021); a identificação das fontes de desinformação (Messaoud, 2021); a regulação dos meios digitais de comunicação (Messaoud, 2021;Neuwirth, 2022;Polyák & Nagy, 2021;Wardle & Derakhshan, 2017) e programas de literacia (Andreatta, 2021;Musi, O'halloran, Aloumpi, Carmi & Yates, 2022;Oji, 2022;Paris, Carmien & Marshall, 2022;Puig, Blanco-Anaya & Pérez-Maceira, 2021;Trninić, 2021;Veletsianos, Houlden, Reid, Hodson & Thompson, 2022).…”
Section: Desordem Informativa No Contexto Da Pandemia De Covid-19unclassified